Urinary Neutrophil Gelatinase-Associated Lipocalin (NGAL) Predicts Renal Function Decline in Patients With Glomerular Diseases - Coppolino, Giuseppe; Comi, Nicola; Bolignano, Davide; Patella, Gemma; Comi, Alessandro; Provenzano, Michele; Rivoli, Laura; Andreucci, Michele; Fuiano, Giorgio (Frontiers in Cell and Developmental Biology, 2020)
Objective Available biomarkers for monitoring primary glomerulonephritides (GNs), often lack the ability to assess longitudinal changes and have great variability with poor sensitivity. Accruing evidence has demonstrated that Neutrophil Gelatinase-Associated Lipocalin (NGAL), holds promising capacities in predicting renal function worsening in various renal diseases. We aimed at analyzing urinary NGAL (uNGAL) levels in a cohort of individuals with biopsy-proven GNs in order to evaluate its ability to reflect the entity of renal damage and to predict disease evolution overtime. Methods We enrolled 61 consecutive GNs patients still naïve to pathogenic therapy. uNGAL levels were measured at baseline and patients prospectively followed until the manifestation of a combined outcome of doubling of baseline serum creatinine and/or end-stage kidney disease requiring permanent dialysis support. Results Median uNGAL levels were 107[35–312] ng/mL. At univariate and multivariate analyses an inverse correlation was found between eGFR and uNGAL levels (p = 0.001). Progressor subjects showed exceedingly increased baseline uNGAL values as compared with non-progressors (p < 0.001). Twenty-one patients (34%) reached the composite renal endpoint. Subjects with uNGAL values above the optimal, ROC-derived, cut-off of 107 ng/mL experienced a more rapid progression to the renal endpoint (p < 0.001; HR: 5.47; 95% CI 2.31–12.95) with a mean follow-up time to progression of 73.4 vs 83.5 months. Conclusion In patients affected by primary glomerulonephritides, uNGAL may represent a real-time indicator of renal damage and an independent predictor of renal disease progression. Further studies on larger populations are warranted to confirm these findings.